Improving the Mathematics Performance of Second-Grade Students with Mathematics Difficulties through an Early Numeracy Intervention. Issue 1 (January 2021) - Bryant, Diane Pedrotty; Pfannenstiel, Kathleen Hughes; Bryant, Brian R.; Roberts, Greg; Fall, Anna-Mari; Nozari, Maryam; Lee, Jihyun
The purpose of this study was to determine the effects of an early numeracy Tier 2 intervention on the mathematics performance of second-grade students with persistent mathematics difficulties. Whole number content and instructional design features were used to boost performance in second-grade early numeracy concepts and skills. Researchers employed a pretest-posttest control group design with randomized assignment of 83 students to the treatment condition and 38 students to the comparison condition. The research team's mathematics interventionists delivered instruction four days per week for 20 weeks to small groups of second-grade students who were identified with persistent mathematics difficulties. Proximal and distal measures were used to determine the effects of the intervention. Findings showed that students in the treatment group outperformed students in the comparison group on the proximal measure of mathematics performance. There were no differences between groups on the problem-solving measures.